2019
DOI: 10.1002/ijgo.12810
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of vaginal laxity symptoms in women attending a urogynecology clinic in Saudi Arabia

Abstract: Objective To evaluate the prevalence of vaginal laxity (VL) and its correlates in a cohort of women attending a urogynecology clinic in a tertiary referral center in Saudi Arabia. Methods In this retrospective study, demographic information, clinical characteristics, and POP‐Q system measurements for women attending the King Fahad Medical City Urogynecology Clinic (January 2013 to April 2015) were analyzed. Women with and without VL were compared across these variables. Results Out of 376 women attending the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 19 publications
1
13
0
1
Order By: Relevance
“…Moreover, in a study conducted on plastic surgery patients, one in six females reported VL and the authors deduced that vaginal deliveries resulted in the development of VL, and VL subsequently predisposed the studied women to the development of sexual distress [49]. Regarding the prevalence of VL, in a local study conducted at a tertiary care center in Riyadh, Saudi Arabia, the prevalence of VL among women attending the urogynecology clinics accounted for 35.9%, which is in line with a study conducted in the UK where the VL prevalence was 38% [8,11]. Standardized definitions and associations between VL, POP and sexual function need to be further studied.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Moreover, in a study conducted on plastic surgery patients, one in six females reported VL and the authors deduced that vaginal deliveries resulted in the development of VL, and VL subsequently predisposed the studied women to the development of sexual distress [49]. Regarding the prevalence of VL, in a local study conducted at a tertiary care center in Riyadh, Saudi Arabia, the prevalence of VL among women attending the urogynecology clinics accounted for 35.9%, which is in line with a study conducted in the UK where the VL prevalence was 38% [8,11]. Standardized definitions and associations between VL, POP and sexual function need to be further studied.…”
Section: Discussionsupporting
confidence: 77%
“…No correlation was detected between VL and POP-Q measurements. Moreover, there was no significant difference in the VL prevalence between participating women belonging to the clinically significant POP (stage 2-4) and non-significant POP (stage 0-1) groups [11].…”
Section: Demographics Risk Factors and Prevalencementioning
confidence: 76%
See 1 more Smart Citation
“…VL is a feeling of excessive vaginal looseness and affects satisfaction during sexual intercourse. A hospital-based study in Saudi Arabia with a much smaller sample reported VL and POP at 35.9% and 45.5%, respectively [ 22 ]. As expected the rate is lower in a community-based study.…”
Section: Discussionmentioning
confidence: 99%
“…Une hyperlaxité vaginale peut être la cause d'une facile pénétration d'air dans la cavité vaginale avec son expulsion lors d'efforts (hyperpression abdominale) ou lors de l'intromission qui va alors mécaniquement chasser l'air de la cavité. L'hyperlaxité vaginale est hautement corrélée à la présence de GV (20). L'hyperlaxité vaginale rapportée par 38% des femmes sur une étude de 2621 patientes consultant en uro-gynécologie (21), est probablement multifactorielle avec des facteurs constitutionnels génétiques, des désinsertions musculaires obstétricales ou les GV sont décrits (22), des atteintes musculaires pelvi-périnéales secondaires à des neuropathies pudendales d'étirement survenant pendant la grossesse ou l'accouchement.…”
Section: Discussionunclassified